Determining the Role of Psychological Hardiness and Resilience in Predicting Psychological Differentiation in Secondary School Girls of Bandar Abbas City - Azita Khanjani; Ashraf Beirami; Moosa Javdan (Journal of Community Health Research)
Background: Considering the importance of mental abilities in continuing education in students, the present study was conducted to determine the role of psychological toughness and resilience in predicting the psychological differentiation of female students of the second level of high school in Bandar Abbas city. Methods: The current research method was a correlational description. The statistical population of the research was made up of all female students of second-secondary education in Bandar Abbas city in the academic year of 2024. Several 380 people were selected as a sample by cluster random sampling method. The research tools were Skorn and Friedlander's self-differentiation questionnaires, Kubasa's psychological toughness, and Connor and Davidson's resilience scale. Data were analyzed using Pearson's correlation test and multivariate regression. Results: The results showed that psychological toughness (R = 0.23 & P < 0.01) and all its components and resilience (R = 0.26 & P < 0.01) and all its components have a positive and significant relationship with psychological differentiation in students. Also, the results of the regression analysis showed that psychological toughness (β = 0.26 & P < 0.01) and resilience (β = 0.30 & P < 0.01) can positively and meaningfully predict differentiation in students. Conclusion: using the results of this research and considering the identification of factors affecting differentiation, it is suggested to pay special attention to the field of increasing the characteristics of psychological toughness and resilience of students.